Feeling Asian Together: Coping with #COVIDRacism on Subtle Asian Traits - Abidin, Crystal; Zeng, Jing (2020)
Since the onset of COVID-19, incidents of racism and xenophobia have been occurring globally, especially toward people of East Asian appearance and descent. In response, this article investigates how an online Asian community has utilized social media to engage in cathartic expressions, mutual care, and discursive activism amid the rise of anti-Asian racism and xenophobia during COVID-19. Specifically, we focus on the 1.7-million-strong Facebook group “Subtle Asian Traits” (SAT). Throughout the COVID-19 pandemic, the 1,200 new posts it publishes daily have swiftly pivoted to the everyday lived experiences of (diaspora) East Asians around the world. In this article, we reflect on our experiences as East Asian diaspora members on SAT and share our observations of meaning-making, identity-making, and community-making as East Asians collectively coping with COVID-19 aggression between January and May 2020.